LEGAL POSITION OF BONDING THE BUYING OF LAND PLOT ABOVE MASTER CERTIFICATE OF LAND PROPRIETARY RIGHTS IN KAMPUNG SUKAMANDI WAY GUBAK BANDAR LAMPUNG - Rissa Afni Martinouva; Linda Panheti; Rendy Renaldy; Aditia Arief Firmanto (PRANATA HUKUM, 2022)
Agreement is a legal relationship regarding property. The types of agreements in civil law consist of many types, one of which is a material agreement such as a plot of land. Land plots are not only carried out by developing business entities that have met the requirements, but are also carried out by individuals. Plots of land by individuals are very helpful for the government in terms of accelerating the equitable distribution of residents' needs for housing. There are also land issues that arise because of the land acquisition process by individuals. These problems are usually expressed by buyers who feel aggrieved. Because there is a discrepancy between what was purchased from the plot holder and what he received later.